El cáncer de seno : conocimientos, actitudes y prácticas para la detección temprana en Amalfi, Antioquia (2019)
ABSTRACT: To characterize informed and traditional knowledge on breast cancer, as well as attitudes, and practices for its early detection among 30 to 69 years old women in the urban area of the municipality of Amalfi, Antioquia. Methodology: Crosssectional study using a survey involving 335 women, selected via simple random sampling using housing addresses provided by the Secretariat for City Planning. Results: The combined score for breast cancer knowledge, risk factors, and symptoms was 14 (standard deviation: 3.6) out of 22 possible points, which shows an intermediate understanding of the topic. In 30 to 49 years old women, 82 % of them knew what breast cancer self-examination was, 14 % knew what clinical breast cancer exams were, and 68 % knew what a mammography was. On the contrary, in 50 to 69 years old women, percentages for the same criteria were 62 %, 10 %, and 63 %, respectively. 95 % of the respondents reported that early detection methods are important for cancer prevention or its timely treatment. 71.9 % of the 39 to 49 years old respondents, as well as 67.1 % of 50 to 69 years old women had already performed breast self-examination. 41.5 % of women had taken a clinical breast exam, without significant differences between age groups. Only 39.2 % of 50 to 69 years old women, had had a mammography. Conclusions: Knowledge on breast cancer, as well as attitudes, and practices for its early detection show deficiencies among the compared age groups; however, women present a favorable disposition towards breast cancer early detection, which may favor a strengthening of knowledge about this type of cancer and engage women in involving themselves in procedures for its detection.